AN ANALYSIS OF DERIVATIONAL AND INFLECTIONAL MORPHEMES OF TENGANAN PEGRINGSINGAN DIALECT - ., Ni Nyoman Trisna Utami; ., Prof. Dr.I Nyoman Adi Jaya Putra, MA; ., I Putu Ngurah Wage M, S.Pd. (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
Penelitian ini bertujuan untuk mendeskripsikan proses derivasi dan infleksi di Dialek Tenganan Pegringsingan (DTP). Penelitian ini merupakan penelitian deskriptif kualitatif. Dua informan dari Tenganan Pegringsingan telah dipilih berdasarkan kriteria yang telah ditentukan. Data dikumpulkan berdasarkan tiga teknik, yaitu: observasi, teknik perekaman dan teknik wawancara (mendengarkan dan mencatat). Hasil penelitian menunjukkan bahwa ada 3 awalan di DTP; awalan ma-, N-, dan a-. Ada tiga jenis akhiran di DTP; akhiran -e, -ang, dan -in. Awalan dan akhiran di Dialek Tenganan Pegringsingan yang termasuk derivasi adalah awalan ma-, N-, and and suffix -ang, dan -in. Awalan dan akhiran di Dialek Tenganan Pegringsingan yang temasuk infleksi adalah awalan N-, and a- and suffix -Ç, -ang, and -in.Kata Kunci : derivasi, morfem infleksi, dialek Tenganan Pegringsingan The study aimed at describing derivational and inflectional processes in Tenganan Pegringsingan Dialect (TPD). This research is a kind of linguistics research which is design in descriptive qualitative research. Two informants sample of TPD were chosen based on a set of criteria. The data were collected based on three techniques, namely observation, recording technique and interview (listening and noting) technique. The result of the study showed that there were three kinds of prefixes in Tenganan Pegringsingan Dialect; prefix ma-, N-, and a-. There were three kinds of suffixes in Tenganan Pegringsingan Dialect; suffix -e, -ang, and -in. Prefixes and suffixes in TPD having derivational process were: prefix ma-, n-, and suffix -ang, and -in. Prefixes and suffixes in TPD having inflectional process were: prefix N-, and a- and suffix -Ç, -ang, and -in.keyword : Derivational, Inflectional, Morpheme and Tenganan Pegringsingan Dialect (TPD)